The mediating effect of purchase intention toward the relationship of attitude, subjective norm, perceived usefulness, trust and online shopping behavior - Lim, Yi Jin
This study was conducted to examine the consumer behavior specifically online shopping behavior of university students aged between 18 and 34 that currently pursuing their studies in University Malaysia Perlis. A total of 800 sets of questionnaires have been distributed and 662 questionnaires were returned and used for coding, analysis and testing the hypothesis. Data for all the study variables were collected through self-administered survey questionnaires and analyzed using SPSS version 18.0 and AMOS version 16.0. Structural Equation Modeling to test the model fits and hypotheses testing. The conclusion could be depicted that attitude and trust positively influenced online purchase intention and shopping behavior while perceived usefulness influenced online purchase intention and shopping behavior in negative way. It is interesting to note that subjective norm positively influenced purchase intention but negatively influenced online shopping behavior. Results also showed that purchase intention positively influenced online shopping behavior. The mediating effect of purchase intention indicated that attitude and online shopping behavior was fully mediated, subjective norm and online shopping behavior is partially mediated, whereas perceived usefulness and trust were not mediated. The results also demonstrated that the hypothesized model was fit and nine hypotheses were supported whereas four hypotheses were rejected. Sample from working adults and other variables that related to online shopping were suggested to be included in future research.